An N‐Acetyl Cysteine Ruthenium Tricarbonyl Conjugate Enables Simultaneous Release of CO and Ablation of Reactive Oxygen Species. Issue 42 (28th August 2015) - Seixas, João D.; Chaves‐Ferreira, Miguel; Montes‐Grajales, Diana; Gonçalves, Ana M.; Marques, Ana R.; Saraiva, Lígia M.; Olivero‐Verbel, Jesus; Romão, Carlos C.; Bernardes, Gonçalo J. L.
Abstract We have designed and synthesised a [Ru(CO)3Cl2(NAC)] pro‐drug that features an N‐acetyl cysteine (NAC) ligand. This NAC carbon monoxide releasing molecule (CORM) conjugate is able to simultaneously release biologically active CO and to ablate the concurrent formation of reactive oxygen species (ROS). Complexes of the general formulae [Ru(CO)3(L)3]2+, including [Ru(CO)3Cl(glycinate)] (CORM‐3), have been shown to produce ROS through a water–gas shift reaction, which contributes significantly, for example, to their antibacterial activity. In contrast, NAC‐CORM conjugates do not produce ROS or possess antibacterial activity. In addition, we demonstrate the synergistic effect of CO and NAC both for the inhibition of nitric oxide (formation) and in the expression of tumour‐necrosis factor (TNF)‐α. This work highlights the advantages of combining a CO‐releasing scaffold with the anti‐oxidant and anti‐inflammatory drug NAC in a unique pro‐drug.